The Effect of Using Information Technology and HR Development on Employee Performance at CV. Prenada Media Group Medan - Audry, Charvolika; Harahap, Kartini (PT FORMOSA CENDEKIA GLOBAL, 2024)
This research aims to examine the influence of the use of information technology and Human Resources (HR) development on employee performance at CV. Prenada Media Group Medan. The research method uses a quantitative approach with multiple linear regression analysis techniques. Data was collected through a survey of 45 employees, and statistical analysis was carried out using the t test, F test, and coefficient of determination test (R2). The research results show that the use of information technology and HR development together has a positive and significant influence on employee performance. These findings are consistent with previous research and contribute to understanding the importance of integrating information technology and human resource development in increasing workforce effectiveness and productivity in the corporate environment.